Functional characterization of the sugarcane (Saccharum spp.) ammonium transporter AMT2;1 suggests a role in ammonium root-to-shoot translocation - Koltun, Alessandra; Maniero, Rodolfo A.; Vitti, Marielle; de Setta, Nathalia; Giehl, Ricardo F. H.; Lima, Joni E.; Figueira, Antonio (Frontiers in Plant Science, 2022)
AMMONIUM TRANSPORTER/METHYLAMMONIUM PERMEASE/RHESUS (AMT) family members transport ammonium across membranes in all life domains. Plant AMTs can be categorized into AMT1 and AMT2 subfamilies. Functional studies of AMTs, particularly AMT1-type, have been conducted using model plants but little is known about the function of AMTs from crops. Sugarcane (Saccharum spp.) is a major bioenergy crop that requires heavy nitrogen fertilization but depends on a low carbon-footprint for competitive sustainability. Here, we identified and functionally characterized sugarcane ScAMT2;1 by complementing ammonium uptake-defective mutants of Saccharomyces cerevisiae and Arabidopsis thaliana. Reporter gene driven by the ScAMT2;1 promoter in A. thaliana revealed preferential expression in the shoot vasculature and root endodermis/pericycle according to nitrogen availability and source. Arabidopsis quadruple mutant plants expressing ScAMT2;1 driven by the CaMV35S promoter or by a sugarcane endogenous promoter produced significantly more biomass than mutant plants when grown in NH4+ and showed more 15N-ammonium uptake by roots and nitrogen translocation to shoots. In A. thaliana, ScAMT2;1 displayed a Km of 90.17 µM and Vmax of 338.99 µmoles h-1 g-1 root DW. Altogether, our results suggest that ScAMT2;1 is a functional high-affinity ammonium transporter that might contribute to ammonium uptake and presumably to root-to-shoot translocation under high NH4+ conditions.